Sources and benefits of vitamin C - Taraj, Krenaida; Hasa, Asela; Muca, Alba (Technium BioChemMed, 2021)
Vitamin C is very important in the diet of each individual, so it is important to make each of us aware of the sources of Vitamin C in the food products we consume, the recommended daily dose and cases of taking Vitamin C through supplements. Based on the processed data of the questionnaire we can say that 69% of the sample stated that they intend to get Vitamin C through the diet. Also, 43% of the sample say that they increase the use of food products which contain Vitamin C during the winter season in order to protect themselves from seasonal viruses. 74% of the sample stated that the presence of Vitamin C in certain food products influences their decision to consume certain food products.51% of the sample stated that they would increase the consumption of products that contain Vitamin C as a result of the information they would have about the product. 64% of the sample stated that they have increased the consumption of food products that contain Vitamin C during the Covid-19 situation, and 43% of the sample stated that sometimes they intend to include in their children's diet products that contain Vitamin C.